Increased Sensory Inputs Through Productive Learning Tasks To Enhance The Short-Term Memory Capacity: An Alternative To Nootropics - et. al., Chawasit Pattaraphongplin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nootropics are drugs that have been used as cognitive enhancers that many take to improve memory and mental alertness. However, taking any type of drug is likely to be associated with some risk either physiologically or psychologically. This study offers an alternative approach to this excess reliance on medication, that is the use of increased sensory inputs through productive skills to enhance the short-term memory capacity. There are times when a short attention span and an ineffective retention ability are caused by unengaging instructional approaches, not physiological factors.An experimental study was conducted among 50 high school students whose ability to remember a set of 10 distinct numbers was tested in two different settings: receptive learning through auditory and visual stimuli and productive learning through auditory and kinesthetic stimuli. The results showed that by incorporating the productive skills (i.e., speaking and writing), students’ short-term memory of the numeric informationwas improved significantly at the statistical level of 95%. It therefore suggests that before deciding to take any medication, the first attempt to be made to help students concentrate more on learning and enhance their memory capacity is to intensify sensory inputs through the productive skills, rather than leaving them exposed only to the receptive tasks.